Rate control in DCT video coding for low-delay communications - Ribas-Corbera, J; Lei, Shawmin (IEEE transactions on circuits and systems for video technology, 1999)
An important motivation for the development of the emerging H.263+ and MPEG-4 coding standards is to enhance the quality of highly compressed video for two-way, real-time communications. In these applications, the delay produced by bits accumulated in the encoder buffer must be very small, typically below 100 ms, and the rate control strategy is responsible for encoding the video with high quality and maintaining a low buffer delay. In this work, we present a simple rate control technique that achieves these two objectives by smartly selecting the values of the quantization parameters in typical discrete cosine transform video coders. To do this, we derive models for bit rate and distortion in this type of coders, in terms of the quantization parameters. Using Lagrange optimization, we minimize distortion subject to the target bit constraint, and obtain formulas that indicate how to choose the quantization parameters. We implement our technique in H.263 and MPEG-4 coders, and compare its performance to TMN7 and VM7 rate control when the encoder buffer is small, for a variety of video sequences and bit rates. This new method has been adopted as a rate control tool in the test model TMN8 of H.263+ and (with some modifications) in the verification model VM8 of MPEG-4.